2019
DOI: 10.1101/cshperspect.a035634
|View full text |Cite
|
Sign up to set email alerts
|

Specification of the First Mammalian Cell Lineages In Vivo and In Vitro

Abstract: Our understanding of how the first mammalian cell lineages arise has been shaped largely by studies of the preimplantation mouse embryo. Painstaking work over many decades has begun to reveal how a single totipotent cell is transformed into a multilayered structure representing the foundations of the body plan. Here, we review how the first lineage decision is initiated by epigenetic regulation but consolidated by the integration of morphological features and transcription factor activity. The establishment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 206 publications
(267 reference statements)
0
10
0
Order By: Relevance
“…The TE cell lineage, with the specific expression of Cdx2 and Gata3, contributes to the placenta; while the ICM cells, marked by the expression of pluripotent factors such as Oct4, Nanog, and Sox2, differentiate into epiblast and primitive endoderm, which eventually give rise to all embryonic tissues and some extraembryonic membranes, respectively [40,41]. During the first cell lineage differentiation, the Hippo pathway controls the TE lineage specification [42][43][44]45], while epigenetic modifications are involved in the consolidation of the ICM cell lineage [46,47]. A recent study suggested that asymmetric distribution of Carm1-deposited dimethyl-arginine 26 of histone H3 (H3R26me2) in the blastomeres is observed as early as four-cell stage embryos [48].…”
Section: Epigenetic Regulation Of Icm and Te Lineage Specificationmentioning
confidence: 99%
“…The TE cell lineage, with the specific expression of Cdx2 and Gata3, contributes to the placenta; while the ICM cells, marked by the expression of pluripotent factors such as Oct4, Nanog, and Sox2, differentiate into epiblast and primitive endoderm, which eventually give rise to all embryonic tissues and some extraembryonic membranes, respectively [40,41]. During the first cell lineage differentiation, the Hippo pathway controls the TE lineage specification [42][43][44]45], while epigenetic modifications are involved in the consolidation of the ICM cell lineage [46,47]. A recent study suggested that asymmetric distribution of Carm1-deposited dimethyl-arginine 26 of histone H3 (H3R26me2) in the blastomeres is observed as early as four-cell stage embryos [48].…”
Section: Epigenetic Regulation Of Icm and Te Lineage Specificationmentioning
confidence: 99%
“…The blastocyst formation is an important cellular event during preimplantation embryonic development. Concomitantly, the first cell segregation generates pluripotent and differentiating lineages, leading to the formation of ICM and TE in blastocysts ( Chazaud and Yamanaka, 2016 ; White and Plachta, 2020 ). The first lineage specification is tightly regulated by the restricted expression of master transcription factors ( Rossant, 2018 ) and signaling pathways ( Menchero et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilized embryos undergo several cell divisions to give rise to blastocysts. Concomitant with blastocyst formation, the trophectoderm (TE) and inner cell mass (ICM) lineages are generated ( Chazaud & Yamanaka, 2016 ; White & Plachta, 2020 ). The establishment of a functional TE epithelium is essential for blastocyst formation.…”
Section: Introductionmentioning
confidence: 99%